Promotion Strategy And The Impact Of Covid-19 On Msme (Micro, Small And Medium Enterprises) In Lubuklingga - Ronal, Ronal Aprianto (Adpebi Science Series, 2022)
The problem in this research was how the impact of covid-19 on micro, small and medium enterprises at food and beverage industry in Lubuklinggau and how to overcome the impact of covid-19 on micro, small and medium enterprises at food and beverage industry in Lubuklinggau . This study uses qualitative methods, data collection technique by using observation, interviews and documentation. This study aims to determine the impact and how to overcome the impact of covid-19 on micro, small and medium enterprises in Lubuklinggau. The results of research and discussion conducted on several micro, small and medium business in Lubuklinggau, almost all of the micro, small and medium enterprises have felt the impact of the COVID-19 pandemic, such as decreased sales turnover and they need appropriate promotion strategies to increase their income